2020
DOI: 10.1186/s40662-020-00179-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in higher order aberrations after central corneal regularization - a comparative two-year analysis of a semi-automated topography-guided photorefractive keratectomy combined with corneal cross-linking

Abstract: Background: The optical quality in progressive keratoconus deteriorates due to ectasia and distortion of the corneal shape and optics. While corneal cross-linking (CXL) aims at stopping disease progression, "CXL-Plus" combines CXL with excimer laser ablation to improve visual function. Central Corneal Regularization (CCR) represents a therapeutic excimer laser modality specifically designed to smoothen the ectatic corneal shape and to reduce higher order aberrations (HOA). We set out to compare CXL-Plus, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, the failure of these refractive corrections in KCN patients was explained by the increased HOAs 17 . The normal value of total HOAs in the healthy population is around 0.30µm, however, several studies detected higher HOAs in KCN patients ranging between 0.71-10.94µm 12, 18,19 . The mean of preoperative HOAs was 1.62±0.57 µm in our study.…”
Section: Discussionmentioning
confidence: 97%
“…However, the failure of these refractive corrections in KCN patients was explained by the increased HOAs 17 . The normal value of total HOAs in the healthy population is around 0.30µm, however, several studies detected higher HOAs in KCN patients ranging between 0.71-10.94µm 12, 18,19 . The mean of preoperative HOAs was 1.62±0.57 µm in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, evaluation of both anterior and posterior corneal surface HOAs allows increased understanding of the optical quality of keratoconic eyes [20]. In studies by Hassan and Iselin et al, aberrations of the posterior corneal surface did not change at 7 and 24 months after CCL [6,21]. In the present study, higher-order aberrations of the posterior corneal surface did not signi cantly change in a post-CCL follow-up period of 36 months similar to the study by Iselin et al Greenstein et al compared HOA changes at 1 year post-CCL between crosslinked and control ectatic eyes, and concluded that there was a mean decrease in posterior corneal HOAs in the treatment group while there was a mean increase in the control group [22].…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection criteria are described in detail elsewhere [5]. In summary, we analyzed patients treated for progressive keratoconus using a uniform CXL protocol without any other diseases affecting visual function.…”
Section: Patientsmentioning
confidence: 99%
“…In a recent matched group analysis, we were able to show that CXL plus reduces higher-order aberrations and the steepest radius of anterior curvature (K max ) more effectively than CXL only [5]. The matching of datasets balanced the distribution of covariates, making the two groups differ only randomly with respect to all covariates and therefore allowing a clear statement regarding the efficiency of CXL plus.…”
Section: Introductionmentioning
confidence: 99%